Active School Travel the Associations between Perceptions of Road Safety and Active Travel for School Children and Their Parents - a Health Needs Assessment. (June 2017) - Howard, Rob
Abstract : Background: This Health Needs Assessment focuses on children aged 5–15 years old who attend primary or secondary school in Leicestershire and Rutland (maintained, free and academy). The aim was to understand the perceptions of road safety and road traffic injuries associated with active school travel and how closely these match the real risk in terms of road traffic accidents occurring on the school commute and the benefits in terms of increased physical activity in children. Methods: An epidemiological review and literature review of national and local data was undertaken using information regarding demography, active school travel, walk time to schools, police reported accidents, physical activity and obesity. Stakeholder views were gathered through an electronic active school travel survey and qualitative focus groups with schools in Leicestershire and Rutland. Qualitative focus group sessions took place in four schools across Leicestershire and Rutland (2 primary, 2 secondary) with a total of 13 teachers, 48 students and 21 parents taking part. Results: A large proportion of primary school pupils in Leicestershire and Rutland potentially could travel to school actively based on walking times less than 30 minutes. However this proportion is reduced for secondary schools, particularly in Rutland, where mixed mode transport may be necessary. Focus groups and an online survey of schools identified a number of barriers and enablers involved in active school travel. The main barriers included the distance, weather, attitudes, safety, and time logistics. Enablers included awareness, attitudes of staff students and pupils, logistics and facilities, travel share schemes, school travel plans and sharing good practice. Safety perceptions of children who responded to the travel survey were higher for their current mode used to get to school than other modes, which may prevent uptake. The literature review highlighted evidence for a number of effective interventions and suggests that a programme of work will be required to change school travel behaviour and increase active travel mode choice. A variety of interventions are provided currently across Leicestershire and Rutland, however awareness, capacity, access and future resources are variable and uncertain. Conclusion and Recommendations: From the evidence reviewed and the gaps identified a number of recommendations are made. A multiagency group including transport, public health, schools and safety partners as a minimum should be convened who are responsible for developing a policy on active school travel to address the policy recommendations. There are further commissioning recommendations for schools, local authorities, CCGs and the LLR Road safety partnership to consider.